2017
DOI: 10.1101/129460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing methods for detecting multilocus adaptation with multivariate genotype-environment associations

Abstract: 20Identifying adaptive loci can provide insight into the mechanisms underlying local adaptation. 21 Genotype-environment association (GEA) 40. CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
330
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(337 citation statements)
references
References 54 publications
7
330
0
Order By: Relevance
“…For LFMM, there was a decreasing proportion of putatively adaptive SNPs as the genomic sample size increased, while RDA was more conservative with a much shallower slope (significant relationships were not found for other EAA software; Table 1). This follows with a recent simulation study that showed ordination approaches, such as RDA, outperformed univariate approaches when searching for signatures of selection (Forester et al, 2017). Future work should focus on the behaviours of these approaches using data from different organisms, biological samples, genomic samples and parameters within a metaanalysis framework.…”
Section: Variation In Sequencing Approaches and Genome Samplingsupporting
confidence: 60%
“…For LFMM, there was a decreasing proportion of putatively adaptive SNPs as the genomic sample size increased, while RDA was more conservative with a much shallower slope (significant relationships were not found for other EAA software; Table 1). This follows with a recent simulation study that showed ordination approaches, such as RDA, outperformed univariate approaches when searching for signatures of selection (Forester et al, 2017). Future work should focus on the behaviours of these approaches using data from different organisms, biological samples, genomic samples and parameters within a metaanalysis framework.…”
Section: Variation In Sequencing Approaches and Genome Samplingsupporting
confidence: 60%
“…1: N East = eastern population (orange); N North = northern population (green); and N West = western population (blue). and identify adaptation with low rates of false positives and high rates of true positives across a range of demographic histories, sampling designs and sample sizes (Capblancq et al 2018, Forester et al 2018, was used to identify putative adaptive loci across climatic gradients. RDA was implemented following the methodology outlined in Forester et al (2018).…”
Section: Identifying Putative Adaptive Locimentioning
confidence: 99%
“…F ST -values between sampling localities varied in a predictable manner, with localities closer in geographic proximity (and within the same population) having lower values compared to geographically distant sampling localities or those assigned to different populations (Supplementary material Appendix 1 Table A5). Hilaria jamesii's average F ST was low (0.07), which was beneficial for implementing RDA because this value is similar to the structure in the testing dataset used in Forester et al (2018) (i.e. F ST = 0.05).…”
Section: Population Structure and Historymentioning
confidence: 99%
“…More specifically, we aimed at detecting outlier loci associated with types of breeding sites distributed along a water depth gradient: the beach spawning site located in the intertidal zone, the demersal spawning site in shallow water (from 2 to 5 m), and the demersal spawning site in deeper water (from to 10 to 20 meters). As recommended by Forester et al (2018), we used a combination of latent factor mixed models (LFMM; Frichot et al 2013, Frichot & François 2015 and partial redundancy analysis (pRDA; 'rda' function in 'vegan' R package; Lasky et al 2012, Forrester et al 2018 to detect candidate loci.…”
Section: Searching For Signals Of Local Adaptation Pattern Within Thementioning
confidence: 99%